The “Europe – Russia” Dichotomy as an Invented Tradition of Modern Georgian Nationalism - M. W. Kyrchanov (Международная аналитика, 2021)
In the article, the author analyzes the transformation of the dichotomy “Europe – Russia” in contemporary Georgian intellectual discourse as well as strategies and forms of positive and negative ideologization of the West and Russia. We state that the hypertrophied role of European and Russian images in the Georgian discourse has resulted from the belief of elites in the collective West as an alternative to Russian inﬂ uence. We analyze the main strategies of forming a positive image of Europe in Georgian intellectual discourse, believing that the development of European motifs and images by several generations of Georgian intellectuals led to the emergence of a unique Georgian Europeanism and the concept of the “Non Typical European” Georgian nation. The development of European images depends on the formation and promotion of the image of Russia as a universal Other. It is assumed that the negative mythologization of Russia resulted from the historical trauma of the loss of statehood, Georgia’s forced history in the Russian Empire and the USSR, as well as the failures in the Russian-Georgian relations in the post-Soviet period. Overall, the author believes that Russian and European narratives have become invented traditions of Georgian identity that inﬂ uence the strategies of elites in Georgian foreign policy.